Liver transplantation for bile duct injury after open and laparoscopic cholecystectomy. Issue 2 (9th December 2013) - Parrilla, P; Robles, R; Varo, E; Jiménez, C; Sánchez-Cabús, S; Pareja, E; Fabregat, J; Sánchez-Turrión, V; Valdivieso, A; Vazquez, L; Martínez-de Haro, L F; Sánchez-Bueno, F; et al.
Abstract: Background: Bile duct injury (BDI) after cholecystectomy is a serious complication. In a small subset of patients with BDI, failure of surgical or non-surgical management might lead to acute or chronic liver failure. The aim of this study was to review the indications and outcome of liver transplantation (LT) for BDI after open and laparoscopic cholecystectomy. Methods: Patients with BDI after cholecystectomy who were on the waiting list for LT between January 1987 and December 2010 were identified from LT centres in Spain. A standardized questionnaire was sent to each unit for extraction of data on diagnosis, previous treatments, indication and outcome of LT for BDI. Results: Some 27 patients with BDI after cholecystectomy in whom surgical and non-surgical management for BDI failed were scheduled for LT over the 24-year interval. Emergency LT for acute liver failure was indicated in seven patients, all after laparoscopic cholecystectomy. Two patients died while on the waiting list and only one patient survived more than 30 days after LT. Elective LT for secondary biliary cirrhosis after a failed hepaticojejunostomy was performed in 13 patients after open and seven after laparoscopic cholecystectomy. One patient from the elective transplantation group died within 30 days of LT. The estimated 5-year overall survival rate was 68 per cent. Conclusion: Emergency LT for acute liver failure was more common in patients with BDI after laparoscopic cholecystectomy, and associated with a poor outcome. Abstract : Final option for acute and chronic liver failure